PENGARUH REKRUTMEN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. FASTGLOBAL BERKAH MANDIRI - Munir Azhari; Munawir Munawir; Egy Aulia Putra (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
The effect of recruitment on employee performance at PT. Fastglobal Berkah Mandiri. Munir Azhari, Munawir and Egi Aulia Putra. This research use quantitative and descriptive. The sample in this study were all employees of PT. Fastglobal Berkah Mandiri, totaling 60 people. The sampling technique in this study was an incidental technique. Total sampling taken as many as 60 employees of PT.Fastglobal Berkah Mandiri as respondents in this study. The results of this study indicate that there is a relationship between recruitment and employee performance as evidenced by the value of r (coefficient) 0.444, the contribution value is 19.7% and the rest is influenced by other variables. While the value of t table for n = 60 is 1,672. So that, t count t table or 3.774 1.672, it can be concluded that the recruitment variable has a partial effect on employee performance.